Graphene-based electrothermal film with high heat-conducting property and chef machine

Through graphene/strontium titanate composite porous film and perfluorosulfonic acid modification technology, the shortcomings of the existing graphene-based electrothermal films in thermal conductivity, electrothermal conversion efficiency, hydrophobicity and self-healing ability are solved, and efficient thermal-electric coordinated regulation and long-term stability of the material are achieved.

CN119922766AInactive Publication Date: 2025-05-02SHENZHEN SANLIDA ELECTRICAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510397275.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing graphene-based electric-thermal films have shortcomings in thermal conductivity, electrothermal conversion efficiency, hydrophobicity and self-healing ability, resulting in uneven heat distribution, high energy consumption, poor environmental adaptability and low durability.

Method used

By designing graphene/strontium titanate composite porous films, the three-dimensional interlocking structure of graphene and the strontium titanate nanowires are used to achieve efficient thermal-electric coordinated regulation. At the same time, perfluorosulfonic acid modification technology is used to build a multi-stage hydrogen bond synergistic system to enhance the hydrophobicity and self-healing ability of the material.

Benefits of technology

It significantly improves the thermal conductivity, electric heat conversion ability and environmental adaptability of the material, achieves efficient and uniform electric heat conversion and thermal mechanical stability, and at the same time extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119922766A_ABST
    Figure CN119922766A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electrothermal materials, and provides a graphene-based electrothermal film with high thermal conductivity, the film is composed of a graphene / strontium titanate composite porous film, poly (3, 4-ethylenedioxythiophene)-poly (styrenesulfonic acid), polyvinyl alcohol, perfluorosulfonic acid D-520 and dimethyl sulfoxide. Wherein the graphene / strontium titanate composite porous film is prepared by adopting an in-situ growth method, and a graphene sheet layer forms a three-dimensional porous structure under the connection action of the strontium titanate nanowire, so that the heat-conducting property is improved. The preparation method comprises the steps of construction of a graphene porous preform, growth of strontium titanate nanowires and formation of a composite film, and uniform distribution and densification are realized through vacuum-assisted impregnation and hot pressing processes. The obtained electrothermal film has excellent heat conduction, electrothermal conversion, hydrophobic and self-healing properties, and can be used as a high-efficiency heating element to be applied to equipment such as a chef machine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electric heating materials, and in particular to a graphene-based electric heating film and a food processor with high thermal conductivity. Background Art

[0002] In the fields of smart heating equipment, flexible electronic devices, wearable medical devices and industrial heating systems, the demand for high-performance electric heating film materials is growing. Especially in application scenarios such as high-efficiency heating, temperature-controlled clothing, smart kitchen appliances and aerospace thermal management, electric heating films are core heating elements. Their thermal conductivity, electrothermal conversion efficiency, mechanical durability and environmental adaptability directly determine the overall performance and service life of the system. Therefore, this field has put forward higher technical requirements for graphene-based electric heating films, including excellent thermal conductivity to ensure rapid and uniform distribution of heat, high electrothermal conversion efficiency to reduce energy consumption, and excellent hydrophobicity to improve environmental adaptability and reduce the impact of humidity on electric heating performance. In addition, with the rapid development of flexible electronics and intelligent manufacturing, electric heating films should also have self-healing properties to enhance their durability and reliability during long-term use and avoid performance degradation caused by micro cracks or damage. Improving the thermal conductivity, electrothermal conversion capability and environmental adaptability of graphene-based electric heating films can not only significantly improve the overall efficiency of the heating system and reduce energy loss, but also expand its application in high-end electronics, medical health, aerospace, smart home appliances and other fields, and promote the technological progress and industrial development of high-performance electric heating materials.

[0003] At present, the research of graphene-based electric heating film has made important progress, but there are still certain technical bottlenecks in thermal conductivity, electrothermal conversion efficiency, hydrophobicity and self-healing ability. For example, the Chinese patent with publication number CN117246023A discloses a method for preparing graphene film, graphene and electric heating floor. Although the high thermal conductivity of graphene is used to improve the overall thermal conductivity of the material, the interface thermal resistance between graphene sheets is large, which limits the lateral heat diffusion efficiency, resulting in the overall thermal conductivity not being fully utilized. In addition, the electrothermal conversion efficiency of existing materials is limited by the conductive network structure of graphene, and the traditional random arrangement or simple stacking method is difficult to form an efficient electron transmission path, resulting in uneven ohmic heating, affecting heating performance and energy utilization. At the same time, the hydrophilicity of the graphene material itself is strong, which causes the electric heating film to be easy to absorb moisture in a humid environment, thereby affecting its stability and long-term service life, and the existing hydrophobic modification method usually reduces the thermal conductivity or mechanical flexibility of the material. In addition, it is difficult for current graphene-based electric heating films to achieve self-healing during use. Once the film is damaged or cracked, it often leads to the attenuation or even failure of the electric heating performance, affecting its long-term reliability. Therefore, how to optimize the arrangement of graphene sheets to reduce the interfacial thermal resistance, enhance the uniformity of the conductive network, and improve the hydrophobicity and self-healing ability of the material through reasonable chemical modification or functional design has become a key technical challenge to improve the comprehensive performance of graphene-based electric heating films. Summary of the invention

[0004] (1) Technical issues solved The purpose of the present invention is to provide a graphene-based electric heating film with high thermal conductivity and a chef machine thereof, so as to solve the problems that the current electric heating film is insufficient in high thermal conductivity, hydrophobicity and self-healing performance.

[0005] (2) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: A graphene-based electric heating film with high thermal conductivity comprises the following raw materials in parts by weight: 2.5-5.0 parts of a graphene / strontium titanate composite porous film, 8.0-12.0 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 6.4-14.4 parts of polyvinyl alcohol, 2.0-3.0 parts of perfluorosulfonic acid D-520, and 3.0-11.0 parts of dimethyl sulfoxide.

[0006] The graphene / strontium titanate composite porous film is composed of graphene sheets arranged along the film plane and strontium titanate nanowires filled between the graphene sheets; The strontium titanate nanowires are uniformly grown on the graphene sheet by in-situ growth; The graphene sheets are connected by strontium titanate nanowires to form a three-dimensional porous film structure.

[0007] Further, the preparation method of the graphene / strontium titanate composite porous film is as follows: by weight, 20 to 30 parts of Sr(OH)2·8H2O and 6.0 to 10.0 parts of TiO2 nanoparticles are dispersed in 15 to 25 parts of anhydrous ethanol, and ultrasonically treated for 30 to 45 minutes to form a uniform suspension; then 0.5 to 2.0 parts of the porous graphene preform is immersed in the above suspension, and vacuum-assisted impregnation is carried out at a pressure of -0.08 to -0.1 MPa for 20-30 min. After impregnation, the graphene loaded with the precursor is transferred to a polytetrafluoroethylene reactor, and 20-25 parts of deionized water and 20-25 parts of 25-28 wt.% liquid ammonia are injected. After sealing, a static hydrothermal reaction is carried out at 170-180°C for 24-36 h. After the reaction is completed, the porous solid film is removed, and then washed with deionized water for 3 times, and finally dried at 40-60°C for 10-20 h to obtain a graphene / strontium titanate composite porous film.

[0008] Furthermore, the preparation method of the graphene porous preform is as follows: first, graphene oxide with a sheet diameter of 10-50 μm is uniformly dispersed in 200-500 mL of deionized water at a concentration of 2-5 mg / mL, and then polystyrene with a particle size of 200-500 nm is added, wherein the mass ratio of graphene oxide to polystyrene at room temperature is (1-3):1, and 0.5-1.5 wt% of boric acid is introduced as a cross-linking enhancer, the system is ultrasonically treated for 30-45 min at 20 kHz by a probe, and the obtained uniform dispersion is then injected into a sand core filtration device loaded with a 0.22 μm polytetrafluoroethylene membrane, and layer-by-layer deposition is performed at a flow rate of 5-10 mL / min under a vacuum degree of -0.085-0.095 MPa to finally obtain a wet film, and then the wet film is transferred to a mixed reducing liquid system, the reducing liquid system consisting of 0.5-1.3 mol / L ascorbic acid and 1-3 mol / L ammonia water, treated at 80-85°C for 6-12h, then washed 3 times with tetrahydrofuran, and finally dried in a vacuum drying oven at 40-50°C to constant weight to obtain a graphene porous preform.

[0009] Furthermore, the mass ratio of graphene to strontium titanate in the graphene / strontium titanate composite porous film is (3.0-7.0):(1.5-4.5); Furthermore, the average diameter of the strontium titanate nanowires is 25-45 nm.

[0010] The present invention proposes a design scheme for a graphene / strontium titanate composite porous film material, which realizes the coordinated regulation of thermal-electrical performance through the in-plane orientation arrangement of two-dimensional graphene sheets and the three-dimensional interpenetrating network of one-dimensional strontium titanate nanowires. Oriented graphene constructs a main path for rapid heat conduction, and the in-situ grown strontium titanate nanowires form a cross-layer thermal bridging structure, which significantly improves the efficiency of interfacial thermal coupling; the continuous conductive network of graphene is combined with the dielectric response characteristics of strontium titanate to form a dynamic carrier transport system, which realizes efficient and uniform electrothermal conversion. A multi-level pore preform is constructed by template-assisted self-assembly combined with radiation cross-linking technology, and an interlocking structure of strontium titanate nanowires with orientation matching is formed between graphene sheets through gradient hydrothermal growth. This preparation process effectively improves the permeability of the precursor and strengthens the heterogeneous interface bonding. The optimized composite material shows a significant improvement in anisotropic thermal conductivity, stable linear electrothermal response characteristics and excellent thermomechanical stability, providing a new structural paradigm for the design of flexible thermal functional materials.

[0011] Furthermore, the mass ratio of the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) to polyvinyl alcohol is 1:(0.8-1.2).

[0012] The present invention also discloses a method for preparing a graphene-based electric heating film with high thermal conductivity, comprising the following steps: S1. Add poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), polyvinyl alcohol, perfluorosulfonic acid D-520, and dimethyl sulfoxide into a reaction kettle, accelerate dissolution at a temperature range of 45-55°C, and obtain a uniform solution after magnetic stirring at a speed of 600-1000 rpm for 1.5-2.5 hours; S2. The uniform solution was injected into the graphene / strontium titanate composite porous film by vacuum-assisted impregnation technology, the vacuum degree was controlled at -0.09~-0.11 MPa, and the number of impregnation-decompression cycles was adjusted to 3~5 times to achieve the infiltration of the dispersed system; S3. Then take out the graphene / strontium titanate composite porous film loaded with uniform solution, dry it in a vacuum drying oven at 50-60°C for 30-60 min, continue to heat to 75-85°C and keep it warm for 30-45 min, and finally dry it in a vacuum environment at 110-130°C for 20-30 min.

[0013] S4. The composite film treated by S3 is densified by hot pressing at a pressure of 6-12 MPa and a temperature of 140-160°C for 10-15 min, and finally a graphene-based electric heating film with high thermal conductivity is obtained.

[0014] The present invention proposes a graphene / strontium titanate composite film system modified with perfluorosulfonic acid, which realizes the coordinated optimization of electrical, thermal and mechanical properties through multi-component interface engineering. Perfluorosulfonic acid resin plays a triple role in the system: 1) as an ionic interface modifier, its sulfonic acid group forms a coordination bond with the hydroxyl group on the surface of strontium titanate to enhance the inorganic / organic interface bonding strength; 2) improves the dispersion state of graphene sheets in the polymer matrix through electrostatic repulsion; 3) constructs an electron conduction channel to form a double continuous conductive path with the electron transport network of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid). The material system adopts a gradient design: the bottom layer is a graphene / strontium titanate porous skeleton, the oriented arrangement of graphene sheets provides the main in-plane heat conduction path, and the strontium titanate nanoparticles improve the lateral thermal resistance through phonon scattering regulation; the middle layer is a poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) / perfluorosulfonic acid composite conductive phase, and the delocalized protons of perfluorosulfonic acid and the π electrons of the conjugated polymer produce a synergistic transport effect; the surface layer is constructed of polyvinyl alcohol to construct a flexible encapsulation network, and its hydroxyl groups form a hydrogen bond interlocking structure with the fluorocarbon chain of perfluorosulfonic acid. In addition, the fluorocarbon chain of perfluorosulfonic acid has natural hydrophobicity, and its distribution on the surface of the material can provide certain hydrophobic properties, reduce moisture intrusion, and improve the environmental stability of the material.

[0015] The present invention also provides a food processor, which comprises at least one heating unit, wherein the heating unit is integrated with an electric heating film prepared by the preparation method as a heating element for realizing a heating function.

[0016] The present invention realizes the coupling enhancement of conductivity, self-healing and mechanical properties by designing a multi-level hydrogen bond synergistic system of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), perfluorosulfonic acid resin and polyvinyl alcohol. In the system, sulfonic acid groups (from conductive polymer ionomers and perfluorosulfonic acid) and hydroxyl groups (polyvinyl alcohol) form a dynamic bonding network, in which the rigid fluorocarbon segments of perfluorosulfonic acid and the flexible carbon chains of polyvinyl alcohol produce microphase separation to construct a rigid and flexible interpenetrating structure. When the material is damaged, the movable sulfonic acid groups of the ionomer drive the hydrogen bond recombination through the proton transition mechanism to achieve in-situ repair of the crack interface; at the same time, the ion clusters of perfluorosulfonic acid act as charge transfer stations to bridge the electron transmission paths between the PEDOT conductive domains, so that the electrical properties are restored synchronously during the healing process. The entangled molecular chains of polyvinyl alcohol not only buffer mechanical stress, but also the gradient distribution of hydroxyl density regulates the healing rate through hydrogen bond reconstruction dynamics. This multi-scale synergistic effect enables the material to maintain the continuity of the conductive network during cyclic damage. At the same time, through the balanced design of chain segment mobility and interface polarity, it breaks through the inverted relationship between mechanical strength and healing efficiency of traditional self-healing materials, providing a new strategy for improving the durability of heating devices.

[0017] (3) Beneficial technical effects 1. The present invention realizes efficient thermal-electric synergistic regulation through the in-plane orientation arrangement of graphene and the three-dimensional interlocking structure of strontium titanate nanowires, breaking through the problems of high interface thermal resistance and non-uniform electrothermal conversion of existing materials. Graphene provides a fast heat conduction channel, and strontium titanate builds a cross-layer thermal bridge, which significantly optimizes the thermal coupling efficiency. At the same time, its dielectric response enhances carrier transport and realizes stable electrothermal conversion. Template self-assembly and gradient hydrothermal growth synergistically optimize the pore structure, improve the precursor permeability and interface bonding force, and give the material excellent anisotropic thermal conductivity, linear electrothermal response and thermomechanical stability, which is suitable for the fields of flexible electronics, thermal management and intelligent heating.

[0018] 2. The present invention constructs a graphene / strontium titanate composite film through perfluorosulfonic acid modification, realizes the coordinated optimization of electrical-thermal-mechanical performance, and breaks through the problem of interface incompatibility of traditional composite materials. Perfluorosulfonic acid acts as an interface bridging agent to enhance the inorganic / organic bonding force, and improves the dispersion of graphene through electrostatic repulsion, thereby optimizing the thermal conductivity path. Its delocalized protons and the π electrons of PEDOT:PSS are synergistically transported to enhance the conductive stability, while the fluorocarbon chain gives the material hydrophobicity and improves environmental durability. This system is suitable for flexible electronics, thermal management and protective materials, and solves the problems of conductivity attenuation, high interface thermal resistance and strong humidity sensitivity of existing materials, providing a long-term stable solution for high-performance electronic devices.

[0019] 3. The present invention breaks through the bottleneck of the difficulty in balancing the mechanical strength and healing efficiency of traditional self-healing materials, and realizes the coordinated optimization of conductivity, mechanical strength and self-healing ability through the sulfonic acid-hydroxyl dynamic bonding network and microphase separation structure. Perfluorosulfonic acid is used as an ionic bridging agent to enhance the charge transfer between PEDOT conductive domains, achieve synchronous recovery of electrical properties after fracture healing, and avoid the problem of irreversible damage to the conductive network in the prior art. The chain entanglement effect of polyvinyl alcohol improves the toughness of the film, and accurately controls the healing rate through the gradient hydrogen bond distribution, so that the material can maintain stable performance after repeated damage, meet the needs of flexible electronic devices for durability, efficient healing and long-term stability, and provide high-reliability solutions for intelligent heating, flexible sensing and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a morphology diagram of the graphene porous preform prepared in Example 1 of the present invention.

[0021] Figure 2 This is a morphology picture of the graphene / strontium titanate composite porous film prepared in Example 1 of the present invention.

[0022] Figure 3 This is a morphology diagram of the graphene-based electric heating film prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0024] Example 1

[0025] A graphene-based electric heating film with high thermal conductivity comprises the following raw materials in parts by weight: 2.5 parts of graphene / strontium titanate composite porous film, 8.0 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 6.4 parts of polyvinyl alcohol, 2.0 parts of perfluorosulfonic acid D-520, and 3.0 parts of dimethyl sulfoxide.

[0026] The graphene / strontium titanate composite porous film consists of graphene sheets arranged along the film plane and strontium titanate nanowires filled between the graphene sheets; the strontium titanate nanowires are uniformly grown on the graphene sheets by an in-situ growth method; and the graphene sheets are connected by the strontium titanate nanowires to form a three-dimensional porous film structure.

[0027] The preparation method of the graphene / strontium titanate composite porous film of the present embodiment is as follows: in parts by weight, 20 parts of Sr(OH)2·8H2O and 6.0 parts of TiO2 nanoparticles are dispersed in 15 parts of anhydrous ethanol, and ultrasonically treated for 30 minutes to form a uniform suspension; then 0.5 parts of the graphene porous preform is immersed in the above suspension, and impregnated at a pressure of -0.08MPa for 20 minutes by vacuum-assisted impregnation. After impregnation, the graphene loaded with the precursor is transferred to a polytetrafluoroethylene reactor, and 20 parts of deionized water and 20 parts of 25wt.% liquid ammonia are injected. After sealing, a static hydrothermal reaction is carried out at 170°C for 24 hours; after the reaction is completed, the porous solid film is taken out, and then washed with deionized water 3 times, and finally dried at 40°C for 10 hours to obtain the graphene / strontium titanate composite porous film.

[0028] The preparation method of the graphene porous preform of the present embodiment is as follows: first, graphene oxide with a sheet diameter of 10 μm is uniformly dispersed in 200 mL of deionized water at a concentration of 2 mg / mL, and then polystyrene with a particle size of 200 nm is added, wherein the mass ratio of graphene oxide to polystyrene at room temperature is 1:1, and 0.5 wt% of boric acid is introduced as a cross-linking enhancer. The system is ultrasonically treated for 30 min at 20 kHz by a probe, and the obtained uniform dispersion is then injected into a sand core filtration device loaded with a 0.22 μm polytetrafluoroethylene membrane, and layer-by-layer deposition is performed at a flow rate of 5 mL / min under a vacuum degree of -0.085 MPa to finally obtain a wet film, and then the wet film is transferred to a mixed reducing liquid system, the reducing liquid system is composed of 0.5 mol / L ascorbic acid and 1 mol / L ammonia water, and the treatment is continued at 80° C. for 6 h, and then washed 3 times with tetrahydrofuran, and finally dried in a vacuum drying oven at 40° C. to constant weight to obtain a graphene porous preform.

[0029] The mass ratio of graphene to strontium titanate in the graphene / strontium titanate composite porous film of this embodiment is 3.0:1.5; The average diameter of the strontium titanate nanowires in this embodiment is 25 nm.

[0030] A method for preparing a graphene-based electric heating film with high thermal conductivity in this embodiment includes the following steps: S1. poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), polyvinyl alcohol, perfluorosulfonic acid D-520, and dimethyl sulfoxide were added to a reaction kettle, and the dissolution was accelerated at a temperature of 45°C, and a uniform solution was obtained after magnetic stirring at a speed of 600 rpm for 1.5 hours; S2. The uniform solution was injected into the graphene / strontium titanate composite porous film by vacuum-assisted impregnation technology, the vacuum degree was controlled at -0.09 MPa, and the number of impregnation-decompression cycles was adjusted 3 times to achieve the infiltration of the dispersed system; S3. Then take out the graphene / strontium titanate composite porous film loaded with uniform solution, dry it in a vacuum drying oven at 50°C for 30 minutes, continue to heat it to 75°C and keep it warm for 30 minutes, and finally dry it in a vacuum environment at 110°C for 20 minutes.

[0031] S4. The composite film treated by S3 is densified by hot pressing at a pressure of 6 MPa and a temperature of 140°C for 10 minutes, and finally a graphene-based electric heating film with high thermal conductivity is obtained.

[0032] Figure 1 The morphological features of the graphene sheets in the graphene porous preform are shown to be arranged along the planar direction, proving that the material has the advantage of oriented arrangement in structural design, which helps to improve the electrical and thermal conductivity. Figure 2 The microstructure of the graphene / strontium titanate composite porous film was further demonstrated, in which strontium titanate nanowires were evenly distributed between graphene sheets through in-situ growth, and a three-dimensional porous network structure was constructed under their connection. This structure not only enhanced the interface bonding strength and thermal conductivity, but also optimized the overall mechanical stability and humidity adaptability. Figure 3 The final graphene-based electric heating film is shown to have a denser structure, indicating that subsequent process optimization further improves the overall performance of the material, including better electrothermal conversion efficiency and environmental stability. These results together demonstrate the effectiveness of the present invention in material design and performance optimization.

[0033] Example 2

[0034] A graphene-based electric heating film with high thermal conductivity comprises the following raw materials in parts by weight: 3.3 parts of graphene / strontium titanate composite porous film, 9.2 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 8.8 parts of polyvinyl alcohol, 2.3 parts of perfluorosulfonic acid D-520, and 5.4 parts of dimethyl sulfoxide.

[0035] The graphene / strontium titanate composite porous film consists of graphene sheets arranged along the film plane and strontium titanate nanowires filled between the graphene sheets; the strontium titanate nanowires are uniformly grown on the graphene sheets by an in-situ growth method; and the graphene sheets are connected by the strontium titanate nanowires to form a three-dimensional porous film structure.

[0036] The preparation method of the graphene / strontium titanate composite porous film of the present embodiment is as follows: in parts by weight, 23 parts of Sr(OH)2·8H2O and 7.2 parts of TiO2 nanoparticles are dispersed in 18 parts of anhydrous ethanol, and ultrasonically treated for 35 minutes to form a uniform suspension; then 0.9 parts of the graphene porous preform is immersed in the above suspension, and impregnated at a pressure of -0.09 MPa for 23 minutes by vacuum-assisted impregnation. After impregnation, the graphene loaded with the precursor is transferred to a polytetrafluoroethylene reactor, and 21 parts of deionized water and 21 parts of 26wt.% liquid ammonia are injected. After sealing, a static hydrothermal reaction is carried out at 173°C for 28 hours; after the reaction is completed, the porous solid film is taken out, and then washed with deionized water 3 times, and finally dried at 46°C for 13 hours to obtain the graphene / strontium titanate composite porous film.

[0037] The preparation method of the graphene porous preform of this embodiment is as follows: first, graphene oxide with a sheet diameter of 22 μm is uniformly dispersed in 290 mL of deionized water at a concentration of 3 mg / mL, and then polystyrene with a particle size of 290 nm is added, wherein the mass ratio of graphene oxide to polystyrene at room temperature is 1.6:1, and 0.8 wt% of boric acid is introduced as a cross-linking enhancer. The system is ultrasonically treated for 35 min at 20 kHz by a probe, and the obtained uniform dispersion is then injected into a 0. A sand core filtration device with a 22μm polytetrafluoroethylene membrane was used to carry out layer-by-layer deposition at a flow rate of 6.5mL / min under a vacuum degree of -0.088MPa to finally obtain a wet film, which was then transferred to a mixed reducing liquid system consisting of 0.7mol / L ascorbic acid and 1.6mol / L ammonia water. The treatment was continued at 81°C for 8h, and then washed three times with tetrahydrofuran. Finally, the film was dried in a vacuum drying oven at 43°C to constant weight to obtain a graphene porous preform.

[0038] The mass ratio of graphene to strontium titanate in the graphene / strontium titanate composite porous film of this embodiment is 4.2:2.4; The average diameter of the strontium titanate nanowires in this embodiment is 31 nm.

[0039] A method for preparing a graphene-based electric heating film with high thermal conductivity in this embodiment includes the following steps: S1. poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), polyvinyl alcohol, perfluorosulfonic acid D-520, and dimethyl sulfoxide were added to a reaction kettle, and the dissolution was accelerated at a temperature of 48°C, and a uniform solution was obtained after magnetic stirring at a speed of 720 rpm for 1.8 hours; S2. The uniform solution was injected into the graphene / strontium titanate composite porous film by vacuum-assisted impregnation technology, the vacuum degree was controlled at -0.10 MPa, and the number of impregnation-decompression cycles was adjusted 4 times to achieve the infiltration of the dispersed system; S3. Then, the graphene / strontium titanate composite porous film loaded with the uniform solution was taken out, dried in a vacuum drying oven at 53°C for 39 minutes, then heated to 78°C for 34 minutes, and finally dried in a vacuum environment at 116°C for 23 minutes.

[0040] S4. The composite film treated by S3 was densified by hot pressing at a pressure of 8 MPa and a temperature of 146°C for 11 minutes, and finally a graphene-based electric heating film with high thermal conductivity was obtained.

[0041] Example 3

[0042] A graphene-based electric heating film with high thermal conductivity comprises the following raw materials in parts by weight: 4.0 parts of a graphene / strontium titanate composite porous film, 10.4 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 11.2 parts of polyvinyl alcohol, 2.6 parts of perfluorosulfonic acid D-520, and 7.8 parts of dimethyl sulfoxide.

[0043] The graphene / strontium titanate composite porous film consists of graphene sheets arranged along the film plane and strontium titanate nanowires filled between the graphene sheets; the strontium titanate nanowires are uniformly grown on the graphene sheets by an in-situ growth method; and the graphene sheets are connected by the strontium titanate nanowires to form a three-dimensional porous film structure.

[0044] The preparation method of the graphene / strontium titanate composite porous film of the present embodiment is as follows: in parts by weight, 26 parts of Sr(OH)2·8H2O and 8.4 parts of TiO2 nanoparticles are dispersed in 21 parts of anhydrous ethanol, and ultrasonically treated for 39 minutes to form a uniform suspension; then 1.4 parts of the graphene porous preform are immersed in the above suspension, and vacuum-assisted impregnation is performed at a pressure of -0.09 MPa for 26 minutes. After impregnation, the graphene loaded with the precursor is transferred to a polytetrafluoroethylene reactor, and 23 parts of deionized water and 23 parts of 27wt.% liquid ammonia are injected. After sealing, a static hydrothermal reaction is carried out at 176°C for 31 hours; after the reaction is completed, the porous solid film is taken out, and then washed with deionized water 3 times, and finally dried at 52°C for 16 hours to obtain the graphene / strontium titanate composite porous film.

[0045] The preparation method of the graphene porous preform of this embodiment is as follows: first, graphene oxide with a sheet diameter of 34 μm is uniformly dispersed in 380 mL of deionized water at a concentration of 4 mg / mL, and then polystyrene with a particle size of 380 nm is added, wherein the mass ratio of graphene oxide to polystyrene at room temperature is 2.2:1, and 1.1 wt% of boric acid is introduced as a cross-linking enhancer. The system is ultrasonically treated for 39 min at 20 kHz by a probe, and the obtained uniform dispersion is then injected into a 0 .22μm polytetrafluoroethylene membrane was deposited layer by layer at a flow rate of 8mL / min under a vacuum degree of -0.091MPa to finally obtain a wet film, which was then transferred to a mixed reducing liquid system consisting of 1.0mol / L ascorbic acid and 2.2mol / L ammonia water. The treatment was continued at 82°C for 9h, and then washed with tetrahydrofuran for 3 times. Finally, it was dried in a vacuum drying oven at 46°C to constant weight to obtain a graphene porous preform.

[0046] The mass ratio of graphene to strontium titanate in the graphene / strontium titanate composite porous film of this embodiment is 5.4:3.3; The average diameter of the strontium titanate nanowires in this embodiment is 37 nm.

[0047] A method for preparing a graphene-based electric heating film with high thermal conductivity in this embodiment includes the following steps: S1. poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), polyvinyl alcohol, perfluorosulfonic acid D-520, and dimethyl sulfoxide were added to a reaction kettle, and the dissolution was accelerated at a temperature of 51°C. A uniform solution was obtained after magnetic stirring at a speed of 840 rpm for 2.1 hours; S2. The uniform solution was injected into the graphene / strontium titanate composite porous film by vacuum-assisted impregnation technology, the vacuum degree was controlled at -0.10 MPa, and the number of impregnation-decompression cycles was adjusted 4 times to achieve the infiltration of the dispersed system; S3. Then, the graphene / strontium titanate composite porous film loaded with the uniform solution was taken out, dried in a vacuum drying oven at 56°C for 48 minutes, then heated to 81°C and kept warm for 39 minutes, and finally dried in a vacuum environment at 122°C for 26 minutes.

[0048] S4. The composite film treated by S3 is densified by hot pressing at a pressure of 10 MPa and a temperature of 152°C for 13 minutes, and finally a graphene-based electric heating film with high thermal conductivity is obtained.

[0049] Example 4

[0050] A graphene-based electric heating film with high thermal conductivity comprises the following raw materials in parts by weight: 5.0 parts of a graphene / strontium titanate composite porous film, 12.0 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 14.4 parts of polyvinyl alcohol, 3.0 parts of perfluorosulfonic acid D-520, and 11.0 parts of dimethyl sulfoxide.

[0051] The graphene / strontium titanate composite porous film consists of graphene sheets arranged along the film plane and strontium titanate nanowires filled between the graphene sheets; the strontium titanate nanowires are uniformly grown on the graphene sheets by an in-situ growth method; and the graphene sheets are connected by the strontium titanate nanowires to form a three-dimensional porous film structure.

[0052] The preparation method of the graphene / strontium titanate composite porous film of the present embodiment is as follows: by weight, 30 parts of Sr(OH)2·8H2O and 10.0 parts of TiO2 nanoparticles are dispersed in 25 parts of anhydrous ethanol, and ultrasonically treated for 45 minutes to form a uniform suspension; then 2.0 parts of the graphene porous preform are immersed in the above suspension, and vacuum-assisted impregnation is performed at a pressure of -0.1MPa for 30 minutes. After impregnation, the graphene loaded with the precursor is transferred to a polytetrafluoroethylene reactor, and 25 parts of deionized water and 25 parts of 28wt.% liquid ammonia are injected. After sealing, a static hydrothermal reaction is carried out at 180°C for 36 hours; after the reaction is completed, the porous solid film is taken out, and then washed with deionized water 3 times, and finally dried at 60°C for 20 hours to obtain the graphene / strontium titanate composite porous film.

[0053] The preparation method of the graphene porous preform of this embodiment is as follows: first, graphene oxide with a sheet diameter of 50 μm is uniformly dispersed in 500 mL of deionized water at a concentration of 5 mg / mL, and then polystyrene with a particle size of 500 nm is added, wherein the mass ratio of graphene oxide to polystyrene at room temperature is 3:1, and 1.5 wt% of boric acid is introduced as a cross-linking enhancer. The system is ultrasonically treated for 45 min at 20 kHz by a probe, and the obtained uniform dispersion is then injected into a 0. A sand core filtration device with a 22μm polytetrafluoroethylene membrane is used to carry out layer-by-layer deposition at a flow rate of 10mL / min under a vacuum degree of -0.095MPa to finally obtain a wet film, which is then transferred to a mixed reducing liquid system consisting of 1.3mol / L ascorbic acid and 3mol / L ammonia water. The treatment is continued at 85°C for 12h, and then washed three times with tetrahydrofuran. Finally, the film is dried in a vacuum drying oven at 50°C to constant weight to obtain a graphene porous preform.

[0054] The mass ratio of graphene to strontium titanate in the graphene / strontium titanate composite porous film of this embodiment is 7.0:4.5; The average diameter of the strontium titanate nanowires in this embodiment is 45 nm.

[0055] A method for preparing a graphene-based electric heating film with high thermal conductivity in this embodiment includes the following steps: S1. poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), polyvinyl alcohol, perfluorosulfonic acid D-520, and dimethyl sulfoxide were added to a reaction kettle, and the dissolution was accelerated at a temperature of 55°C. A uniform solution was obtained after magnetic stirring at a speed of 1000 rpm for 2.5 hours; S2. The uniform solution was injected into the graphene / strontium titanate composite porous film by vacuum-assisted impregnation technology, the vacuum degree was controlled at -0.11 MPa, and the number of impregnation-decompression cycles was adjusted 5 times to achieve the infiltration of the dispersed system; S3. Then, the graphene / strontium titanate composite porous film loaded with the uniform solution was taken out, dried in a vacuum drying oven at 60°C for 60 min, then heated to 85°C and kept warm for 45 min, and finally dried in a vacuum environment at 130°C for 30 min.

[0056] S4. The composite film treated by S3 is densified by hot pressing at a pressure of 12 MPa and a temperature of 160°C for 15 minutes, and finally a graphene-based electric heating film with high thermal conductivity is obtained.

[0057] Comparative Example 1 The method is basically the same as Example 1, except that perfluorosulfonic acid D-520 is not used.

[0058] Comparative Example 2 The method is basically the same as Example 1, except that no polyvinyl alcohol is added.

[0059] Comparative Example 3 The method is basically the same as Example 1, except that the gradient hydrothermal growth of strontium titanate nanowires is not performed, but an equal amount of graphene porous preform is used to replace the graphene / strontium titanate composite porous film.

[0060] Comparative Example 4 It is basically the same as Example 1, except that the hot pressing process is not used for densification.

[0061] Comparative Example 5 It is basically the same as Example 1, except that disordered stacked graphene sheets are used instead of the oriented structure, and there is no strontium titanate nanowire filling.

[0062] The preparation method of the graphene porous preform of this comparative example is as follows: first, graphene oxide with a sheet diameter of 50 μm is dispersed in 500 mL of deionized water at a concentration of 7 mg / mL, and then polystyrene with a particle size of 900 nm is added, wherein the mass ratio of graphene oxide to polystyrene at room temperature is 1:5, the system is ultrasonically treated for 12 min at 15 kHz and 100 W by a probe to form a non-uniform dispersion, and then the suspension is injected into an open mold, and naturally settled for 30 hours under vacuum-free conditions, and a primary wet film is formed after the liquid phase evaporates, and then the wet film is transferred to a mixed reducing liquid system, the reducing liquid system consists of 0.1 mol / L ascorbic acid and 0.05 mol / L ammonia water, and intermittently shaken for 24 hours at 50° C., and then tetrahydrofuran is used for three shaking washings (250 rpm×5 min / time), and finally treated for 8 hours at 31° C. and 7.38 MPa in a CO2 supercritical drying device to obtain a disordered stacked structure graphene porous preform.

[0063] Performance Testing: DC conductivity test: Refer to ASTM D257-14 and use the four-probe method to measure the sheet resistance of the electric heating film. Use a Keithley 2400 source meter to apply a constant current, record the voltage drop, and calculate the conductivity. During the test, the ambient humidity (40%±5% RH) and temperature (25℃±2℃) must be controlled to ensure data stability.

[0064] Thermal conductivity test: Referring to ASTM E1461-13, the thermal diffusivity (α) of the film was tested using a Netzsch LFA 467 laser flash spectrometer, and the thermal conductivity (λ=α·Cp·ρ) was calculated by combining the specific heat capacity (Cp) and density (ρ). The test temperature range was set at 25~150℃ to evaluate the thermal conductivity of the film.

[0065] Hydrophobicity and moisture resistance test: According to ASTM D7334 "Contact Angle Measurement Standard", the contact angle of deionized water (5μL droplet, 25℃) was measured using a contact angle meter (Dataphysics OCA 50), and the average value of 10 points was taken; the moisture resistance test referred to IEC 60749-4 "Wet Heat Cycle Test", and the contact angle was re-measured after aging for 1000h in an 85℃ / 85%RH environment, requiring the initial contact angle to be greater than 120° and the attenuation after aging to be less than 10°.

[0066] Humidity stability test: Referring to ASTM D570-98, the electric heating film was placed in a constant temperature and humidity chamber at 85% RH and 60°C (according to IEC 60068-2-78) for 500 hours, and the resistance change rate and electrothermal conversion efficiency were tested every 50 hours to evaluate the stability in a high humidity environment.

[0067] Self-healing test: The blade scratch method was used with a scratch depth of about 20% of the film thickness. An in-situ optical microscope (Keyence VHX-7000) was used to observe the healing process. The scratch width change was recorded every 10 minutes in the healing environment (temperature 60°C / humidity 80%RH). In addition, the electrical self-healing ability test was performed, and the resistance recovery rate of the scratched area was monitored using the four-probe method (Keithley 2400).

[0068] The properties of the electric heating films of Examples 1 to 4 and Comparative Examples 1 to 5 are summarized in Table 1.

[0069] Table 1 Performance of the electric heating films of Examples 1 to 4 and Comparative Examples 1 to 5

[0070] It can be seen from Table 1 that the lack of key components or process optimization will reduce the electrical conductivity, thermal conductivity, humidity stability and self-healing ability of the material to varying degrees. Among them, the optimization of interface bonding strength, structural density and orientation arrangement has a particularly significant impact on the overall performance.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A graphene-based electric heating film with high thermal conductivity, characterized in that: The invention comprises the following raw materials in parts by weight: 2.5-5.0 parts of graphene / strontium titanate composite porous film, 8.0-12.0 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 6.4-14.4 parts of polyvinyl alcohol, 2.0-3.0 parts of perfluorosulfonic acid D-520, and 3.0-11.0 parts of dimethyl sulfoxide; The graphene / strontium titanate composite porous film is composed of graphene sheets arranged along the film plane and strontium titanate nanowires filled between the graphene sheets; The strontium titanate nanowires are uniformly grown on the graphene sheet by in-situ growth; The graphene sheets are connected by strontium titanate nanowires to form a three-dimensional porous film structure.

2. A graphene-based electric heating film with high thermal conductivity as claimed in claim 1, characterized in that: The preparation method of the graphene / strontium titanate composite porous film is as follows: by weight, 20-30 parts of Sr(OH)2·8H2O and 6.0-10.0 parts of TiO2 nanoparticles are dispersed in 15-25 parts of anhydrous ethanol, and ultrasonically treated for 30-45 minutes to form a uniform suspension; Subsequently, 0.5 to 2.0 parts of the graphene pre-porous body are immersed in the above suspension, and the impregnation is performed by vacuum assisted impregnation at a pressure of -0.08 to -0.1 MPa for 20 to 30 minutes. After impregnation, the graphene loaded with the precursor is transferred to a polytetrafluoroethylene reactor, and 20 to 25 parts of deionized water and 20 to 25 parts of 25 to 28 wt.% liquid ammonia are injected. After sealing, a static hydrothermal reaction is carried out at 170 to 180°C for 24 to 36 hours. After the reaction is completed, the porous solid film is taken out, and then washed with deionized water 3 times, and finally dried at 40 to 60°C for 10 to 20 hours to obtain a graphene / strontium titanate composite porous film.

3. A graphene-based electric heating film with high thermal conductivity as claimed in claim 1, characterized in that: The preparation method of the graphene porous preform is as follows: first, graphene oxide with a sheet diameter of 10-50 μm is uniformly dispersed in 200-500 mL of deionized water at a concentration of 2-5 mg / mL, and then polystyrene with a particle size of 200-500 nm is added, wherein the mass ratio of graphene oxide to polystyrene at room temperature is (1-3):1, and 0.5-1.5 wt% of boric acid is introduced as a cross-linking enhancer, and then an ultrasonic cell disruptor is used for ultrasonic treatment for 30-45 minutes under 20 kHz conditions, and the obtained uniform dispersion is then injected into a sand core filtration device loaded with a 0.22 μm polytetrafluoroethylene membrane, and layer-by-layer deposition is performed at a flow rate of 5-10 mL / min under a vacuum degree of -0.085-0.095 MPa, and finally a wet film is obtained, and then the wet film is transferred to a mixed reducing liquid system, wherein the reducing liquid system consists of 0.5-1.3 mol / L ascorbic acid and 1-3 mol / L ammonia water, treated at 80-85°C for 6-12h, then washed with tetrahydrofuran for 3 times, and finally dried in a vacuum drying oven at 40-50°C to constant weight to obtain a graphene porous preform.

4. A graphene-based electric heating film with high thermal conductivity as claimed in claim 1 or 2, characterized in that: The mass ratio of graphene to strontium titanate in the graphene / strontium titanate composite porous film is (3.0-7.0):(1.5-4.5).

5. A graphene-based electric heating film with high thermal conductivity as claimed in claim 1, characterized in that: The average diameter of the strontium titanate nanowires is 25-45 nm.

6. A graphene-based electric heating film with high thermal conductivity as claimed in claim 1, characterized in that The mass ratio of the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) to polyvinyl alcohol is 1:(0.8-1.2).

7. A method for preparing a graphene-based electric heating film with high thermal conductivity as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Add poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), polyvinyl alcohol, perfluorosulfonic acid D-520, and dimethyl sulfoxide into a reaction kettle, accelerate dissolution at a temperature range of 45-55°C, and obtain a uniform solution after magnetic stirring at a speed of 600-1000 rpm for 1.5-2.5 hours; S2. The uniform solution was injected into the graphene / strontium titanate composite porous film by vacuum-assisted impregnation technology, the vacuum degree was controlled at -0.09~-0.11 MPa, and the number of impregnation-decompression cycles was adjusted to 3~5 times to achieve the infiltration of the dispersed system; S3. Then take out the graphene / strontium titanate composite porous film loaded with uniform solution, dry it in a vacuum drying oven at 50-60°C for 30-60 min, continue to heat to 75-85°C for 30-45 min, and finally dry it in a vacuum environment at 110-130°C for 20-30 min; S4. The composite film treated by S3 is densified by hot pressing at a pressure of 6-12 MPa and a temperature of 140-160°C for 10-15 min, and finally a graphene-based electric heating film with high thermal conductivity is obtained.

8. A food processor, comprising at least one heating unit, wherein the heating unit integrates a graphene-based electric heating film with high thermal conductivity as described in any one of claims 1 to 6 or a graphene-based electric heating film with high thermal conductivity prepared by the preparation method of claim 7 as a heating element for realizing a heating function.

Citation Information

Patent Citations

  • Graphene film preparation method, graphene film and electric heating floor

    CN117246023A

  • Nanowire structures comprising carbon

    CN101563801A

  • SrTiO3 / graphene composite catalyst as well as preparation method and application thereof

    CN105817217A

  • Thermal insulation material and preparation method thereof

    CN107337897A

  • Flexible composite film and preparation method thereof, and flexible pressure sensor and preparation method thereof

    CN111122021A